Chemical and pharmacological evaluation of manglicolous lichen Roccella montagnei Bel em. D. D. Awasthi - Vinay Bharadwaj Tatipamula; Girija Sastry Vedula; A. V. S. Sastry (SpringerOpen, 2019)
Abstract Background Lichen is a composite organism composed of fungus in association with algae or cyanobacteria. Particularly, lichen betide to mangroves are named as manglicolous lichens. From the folklore, lichen extracts were used in the management of many infections and diseases. Results The chemical investigation of acetone extract of manglicolous lichen Roccella montagnei (RM-Ac) yielded nine known metabolites namely divarinolmonomethylether (1), ethyl divaricatinate (2), divarinol (3), orcinol (4), methyl 2,6-dihydroxy-4-methylbenzoate (5), haematommic acid (6), atranol (7), ethyl haematommate (8) and ethyl orsellinate (9). Except 4, all are for the first reported from this species. The RM-Ac and its metabolites (1-9) were screened for antioxidant (DPPH, ABTS and superoxide free radical assays), anti-inflammatory, anticancer (SRB assay using A549, DLD-1, FADU, HeLa and MCF-7) and acute toxicity studies. The pharmacological results showed that compounds 6 and 8 depicted potent inhibitory profile against ABTS free radical (with IC50 value of 40.0 and 40.5 μg/mL, respectively) and protein denaturation (with IC50 value of 435 and 403 μg/mL, respectively). LD50 of RM-Ac was found to be above 2 g/Kg body weight. Moreover, the RM-Ac showed prominent inhibition of formalin-hind albino rat paw oedema at both the tested doses, i.e., 100 and 200 mg/Kg b.w than that of the standard drug (indomethacin). Furthermore, the compounds 6 and 8 exhibited significant degree of specificity against HeLa, FADU and A549; besides, they showed very little degree of specificity against NHME cell line specifying less toxicity to normal cells. Conclusion It can be concluded that the manglicolous lichen R. montagnei has an aptitude to act against free radicals, inflammation and cancer, and the main metabolites responsible for its biological activity are 6 and 8.